The effect of Na2SiO3 on the burning rate of UPRs 268 BQTN resin composite - Mascuk Susilo (Teknik Mesin - Universitas Muhammadiyah Cileungsi, 2025)
: Polyester resin is a resin that is easy to manufacture, and resistant to weather changes and corrosion. However, polyester resin has low fire resistance so additional materials are needed to improve these deficiencies. The purpose of this study was to improve the fire resistance of polyester composites using a matrix (resin 268 BQTN) with the addition of sodium silicate (Na2SiO3) filler. Specimens were made by the hand layup method while the filler was varied based on the weight percentage of the polymer composite itself. Mixing the resin with Na2SiO3 by stirring using a mixer at a speed of 3000rpm for 5 minutes, then leave for 5 minutes to reduce air bubbles. The fire resistance test followed ASTM D 635. The results of the fire test showed an increase in ignition time which increased from 4.83 seconds (without Na2SiO3) to 9.81 seconds (2.5% Na2SiO3); 13.94 seconds (7.5% Na2SiO3) and 17.34 seconds (7.5% Na2SiO3). The ignition time indicates the increase in combustion time which also has an increasing trend to 159.6 second; 180 seconds; 199.8 seconds and 240 seconds. In contrast to the ignition time and combustion time, the combustion rate has the opposite trend, decreasing with increasing sodium silicate (Na2SiO3), which is 2.128 mm/second; 2.4 mm/second; 2.66 mm/second, and 3.2 mm/second. The decrease in combustion rate show that silicate (Na2SiO3) can increase the composite's fire resistance